2014
DOI: 10.20344/amp.5211
|View full text |Cite
|
Sign up to set email alerts
|

Melanoma Maligno Cutâneo: Estudo Retrospetivo de Sete Anos (2006-2012)

Abstract: Acta Med Port 2014 Jul-Aug;27(4):480-488 RESUMOIntrodução: O melanoma maligno é a neoplasia cutânea mais agressiva, e a sua incidência tem vindo a aumentar nas últimas déca-das. A possibilidade de cura depende de um diagnóstico atempado, sendo fundamental o conhecimento da sua epidemiologia para a implementação de programas de prevenção primária e deteção precoce do melanoma. ABSTRACTIntroduction: Malignant melanoma is the most aggressive skin cancer and its incidence has been increasing in recent decades. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…The location of the primary tumour identi ed in this study and its distribution by gender is as expected by previous research and possibly explained by behaviour of sun exposure adopted by men and women (19) (1) (2) (20). Previous national studies have also reported differences in the location of the primary tumour by gender (21).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The location of the primary tumour identi ed in this study and its distribution by gender is as expected by previous research and possibly explained by behaviour of sun exposure adopted by men and women (19) (1) (2) (20). Previous national studies have also reported differences in the location of the primary tumour by gender (21).…”
Section: Discussionsupporting
confidence: 88%
“…Notwithstanding, the data also suggests that most cases are diagnosed at early stages, as described in Portugal and also in Sweden ( 17) (21).…”
Section: Discussionmentioning
confidence: 84%
“…Notwithstanding, the data also suggests that most cases are diagnosed at early stages, as described in Portugal and also in Sweden 17,23 .…”
Section: Discussionmentioning
confidence: 69%
“…The location of the primary tumour identified in this study and its distribution by sex is as expected by previous research and possibly explained by behaviour of sun exposure adopted by men and women 1,2,21,22 . Previous national studies have also reported differences in the location of the primary tumour by sex 23 . Our study has not identified sex as a prognostic factor, contradicting previous research, which has also suggested differential improvements over time, where prognosis of males seem to have improved more due to disparities in instituted treatments 24 .…”
Section: Discussionmentioning
confidence: 94%